Stereoselective Synthesis and Biological Profile of All Stereoisomers of Lactam Analogues of Strigolactones GR24 and GR18. Issue 1 (10th January 2023) - Quinodoz, Pierre; Lumbroso, Alexandre; Lachia, Mathilde; Screpanti, Claudio; Rendine, Stefano; Horoz, Beyza; Bozoflu, Mert; Catak, Saron; Fonné‐Pfister, Raymonde; Hermann, Katrin; De Mesmaeker, Alain
Abstract: Strigolactones (SLs) are signaling molecules involved in plant development and governing interactions with soil microorganisms in the rhizosphere as well as the germination of parasitic weeds. Developing their use in Crop Protection is a promising approach to a sustainable agriculture by mitigating biotic and abiotic stresses. Recently, a new class of lactam analogues of SL has emerged, namely strigolactams, displaying outstanding potency to induce the germination of parasitic weed O. cumana as well as enhanced chemical and soil stability. Herein, we describe the stereoselective synthesis of GR24 and GR18 lactams harnessing the chemistry of chiral keteniminium (KI) salts, in particular the unprecedented reactivity of chloro‐substituted KI, supported by DFT calculations. We disclose subsequently the biological activity on corn of the 32 stereopure strigolactams prepared, highlighting the crucial influence of stereochemistry and lactam substitution, rationalized by docking analyses. Finally, we performed stability studies in soil, which reveal that stereoisomers display very different half‐lives, reflecting the significant impact of stereochemistry on degradation kinetics. Abstract :